„Sex Education”, czyli serial jako źródło wiedzy o świecie młodzieży - Jakubowski , Witold (Studia Edukacyjne, 2020)
Can a TV series be treated as a space for pedagogical discourses? The answer seems obvious. For modern culture pedagogy, it is a reservoir of knowledge about society. TV series is a characteristic phenomenon in contemporary audiovisual culture. It describes our world in a very honest way. At the same time, it talks about problems affecting various social groups, which are often considered to be “not serious” in informal debates. The television series, as an element of popular art, is an interesting and valuable “social document”. The goal of modern education is to develop a reflective critical view of audiovisual products that surround us. A critical look at fictitious images of reality helps us better understand our world that is the most real. The article is a voice in the discussion on the Sex Education series, as an example of the image of today’s youth, their dilemmas and anxieties woven into school reality, as well as their relations with peer groups and parents.